Molecular gated nanoporous anodic alumina for the detection of cocaine - Ribes, Àngela (Sci Rep, 2016)
We present herein the use of nanoporous anodic alumina (NAA) as a suitable support to implement “molecular gates” for sensing applications. In our design, a NAA support is loaded with a fluorescent reporter (rhodamine B) and functionalized with a short single-stranded DNA. Then pores are blocked by the subsequent hybridisation of a specific cocaine aptamer. The response of the gated material was studied in aqueous solution. In a typical experiment, the support was immersed in hybridisation buffer solution in the absence or presence of cocaine. At certain times, the release of rhodamine B from pore voids was measured by fluorescence spectroscopy. The capped NAA support showed poor cargo delivery, but presence of cocaine in the solution selectively induced rhodamine B release. By this simple procedure a limit of detection as low as 5 × 10(−7) M was calculated for cocaine. The gated NAA was successfully applied to detect cocaine in saliva samples and the possible re-use of the nanostructures was assessed. Based on these results, we believe that NAA could be a suitable support to prepare optical gated probes with a synergic combination of the favourable features of selected gated sensing systems and NAA.